Impact of physical activity, protein intake and social network and their combination on the development of frailty. (26th October 2019) - Haider, Sandra; Grabovac, Igor; Drgac, Deborah; Mogg, Christine; Oberndorfer, Moritz; Dorner, Thomas Ernst
Abstract: Background: Frailty is a geriatric condition associated with adverse health outcomes. As physical inactivity, low protein intake and poor social network are known risk factors, we aimed to assess the influence of these parameters and their interaction in an 11-year follow-up study on a Europe-wide level. Methods: Data from the Study on Health, Ageing and Retirement in Europe were used, including 22 226 community-dwelling robust and prefrail persons aged ≥50 years, from 11 countries. Frailty was assessed with the 'Frailty Instrument for Primary care of the Survey of Health, Ageing and Retirement in Europe'. Additionally, self-reported physical activity (PA), protein intake and satisfaction with social network were assessed. The impact of these parameters on the development of frailty was calculated using multivariate cox regressions. Results: Performing no regular PA, was associated with higher hazards ratio (HRs) for frailty compared with performing regular PA [men: 1.90 (95%CI: 1.50–2.42); women: 1.65 (95%CI: 1.25–2.18)]; HRs for low protein intake were 1.16 (95%CI: 0.93–1.46) for men and 1.05 (95%CI: 0.80–1.37) for women. And HR for poor social network were 0.92 (95%CI: 0.74–1.15) for men and 1.72 (95%CI: 1.31–2.27)] for women. In general, persons with a combination of two of the assessed risk factors had a higher risk for frailty compared with those with no or only one of the risk factors. However, no significant synergy index could be found. Conclusion: The results illustrate the importance of PA, but also of nutritional and social network to prevent frailty.